2017
DOI: 10.4300/jgme-d-17-00139.1
|View full text |Cite
|
Sign up to set email alerts
|

Teaching High-Value Care in Pediatrics: A National Survey of Current Practices and Guide for Future Curriculum Development

Abstract: Most pediatrics residency programs responding to a survey lacked formal HVC curricula. There is a desire nationally for HVC education in pediatrics, particularly in a case-based discussion format.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 24 publications
1
11
0
Order By: Relevance
“…[20][21][22][23] Despite these resources, data reveal that only 10% of pediatric program directors and 15% of internal medicine residency programs report having a formal curriculum on HVC. 24,25 In a survey of pediatric residency programs, respondents identified the largest barrier to HVC as a lack of cost transparency. The majority of respondents agreed that their program needed an HVC curriculum, and 90% of respondents reported that they would use a curriculum if one was available.…”
Section: Problem Identificationmentioning
confidence: 99%
See 1 more Smart Citation
“…[20][21][22][23] Despite these resources, data reveal that only 10% of pediatric program directors and 15% of internal medicine residency programs report having a formal curriculum on HVC. 24,25 In a survey of pediatric residency programs, respondents identified the largest barrier to HVC as a lack of cost transparency. The majority of respondents agreed that their program needed an HVC curriculum, and 90% of respondents reported that they would use a curriculum if one was available.…”
Section: Problem Identificationmentioning
confidence: 99%
“…At a time when most pediatric residencies do not have formal curricula on value, High-Value Pediatrics provides an open-access resource that includes interactive case presentation components that are highly desired by both pediatric program directors and chief residents 24 in addition to didactic lectures and a framework for value-focused improvement projects. We know that clinicians have a poor knowledge of the cost of the care they provide, 10 so the results of our curriculum implementation reveal promise.…”
Section: Implications and Next Stepsmentioning
confidence: 99%
“…In most hospitals, the PICU is a high-utilization area where we have reported that high-value care education does not occur as frequently. 27 However, previous projects have demonstrated success in reducing utilization in intensive care settings through standardization approaches similar to ours. 28 Establishing a culture of value, and careful evaluations of testing necessity and choice of testing modality, are important parts of improving the value of care, even in the critical care setting.…”
Section: Discussionmentioning
confidence: 87%
“…12,13 Educational interventions on HVC have been successful at increasing physician awareness of medical costs. [14][15][16][17][18] It has been suggested, in fact, that physician education regarding cost-conscious care and overuse or misuse of diagnostic testing become an additional ACGME general competency for physicians-intraining. 9,19 Studies have shown that physicians and trainees have a poor understanding of pharmaceutical and diagnostic testing costs.…”
Section: Introductionmentioning
confidence: 99%